2019
DOI: 10.1042/bsr20190821
|View full text |Cite
|
Sign up to set email alerts
|

Association ofIL-16gene polymorphisms with the risk of developing type 2 diabetes mellitus in the Chinese Han population

Abstract: Objective: The aim of the present study was to explore the genetic association of single nucleotide polymorphisms (SNPs) in interleukin-16 (IL-16) gene with type 2 diabetes mellitus (T2DM) susceptibility in a Chinese Han population. Methods: In total, 133 T2DM patients and 127 healthy controls matched by age and gender were recruited in the case–control study. IL-16 gene rs4778889 and rs11556218 polymorphisms were genotyped in the two groups via polymerase chain reaction-restriction fragment len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Concomitant, under over dominant model, the presence of TG genotype had significant association with high risk of T2DM disease. A study on a Chinese Han population showed similar results that TG genotype was higher in diabetic patients than the control group (OR 1.7) [4]. As well as the risk of T2DM was higher in patients with G allele rs11556218 (OR = 1.639, 95 % CI = 1.087-2.471) which also like our results after adjusted them by risk factor of T2DM.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Concomitant, under over dominant model, the presence of TG genotype had significant association with high risk of T2DM disease. A study on a Chinese Han population showed similar results that TG genotype was higher in diabetic patients than the control group (OR 1.7) [4]. As well as the risk of T2DM was higher in patients with G allele rs11556218 (OR = 1.639, 95 % CI = 1.087-2.471) which also like our results after adjusted them by risk factor of T2DM.…”
Section: Discussionsupporting
confidence: 88%
“…The triad of inflammation, obesity and insulin-resistance is shown in diabetes and metabolic syndrome [20]. IL-16 as a pro-inflammatory factor could be identified in several inflammatory diseases as allergic rhinitis and T2DM by stimulating of the secretion of different cytokines [4]. In this study, we are studying the association between IL16 rs11556218 T/G polymorphism and the risk of developing T2DM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…in Caucasians [47], diabetes mellitus [48], autoimmune diseases [49,50], endometriosis [45,51], and knee osteoarthritis [52,53]. A meta-analysis published in 2019 focusing only on renal cancer association studies also found no association between rs4778889 and rs11556218 and this disease [54].…”
Section: Discussionmentioning
confidence: 99%